SURFACE CHEMISTRY AND MORPHOLOGY OF POORLY CRYSTALLINE IRON SULFIDES PRECIPITATED IN MEDIA CONTAINING SULFATE-REDUCING BACTERIA - Herbert R.B.; Benner S.G.; Pratt A.R.; Blowes D.W. (My University, 1998)
This study characterizes the surface chemistry and morphology of poorly crystalline iron sulfides precipitated in a chemically defined growth media for sulfate-reducing bacteria. The precipitates were analyzed by X-ray diffractometry (XRD), X-ray photoelectron spectroscopy (XPS) and scanning electron microscopy (SEM). Based on XRD results, the precipitates exhibit only incipient crystallization with a single broad diffraction peak at about 5 #9, characteristic of disordered mackinawite. The iron sulfides generally exhibit a platy habit with particles 100 to 300 nm in diameter; these particles appear often in 1 to 2 μm spherical aggregates. The XPS results indicate that the Fe(2p3/2) spectrum for poorly crystalline iron sulfide can be fitted with Fe(II) and Fe(III) components, both corresponding to Fe-S bond types. The absence of oxide oxygen in the O(1s) spectrum and Fe(III)-O bond types in the Fe(2p3/2) spectrum supports the conclusion that the poorly crystalline iron sulfides are composed of both ferric and ferrous iron coordinated with monosulfide, with lesser amounts of disulfide and polysulfides also present. These results suggest that the precipitates possess a surface composition similar to greigite, with the remaining mineral mass composed of disordered mackinawite.
Keywords: SULFIDE; MACKINAWITE; SULFATE; BACTERIA; SURFACE; SEM; XPS; SPECTROSCOPY